COMPENSATION AND EMPLOYEE PERFORMANCE AT BUKIT RAYA SEKAWAN MINING COMPANY - Pratama, Yudhistira Anugerah; Yulianty, Farida; Kosasih, Kosasih; Kadarisman, Sumeidi; Paramarta, Vip (Jurnal Ekonomi Manajemen, 2025)
This study aims to obtain an analysis of the effect of compensation on employee performance at Bukit Raya Sekawan Mining Company. This study used an associative quantitative approach. The population in this study is all employees at Bukit Raya Sekawan Mining Company, which is as many as 45 people. Then, the data collection techniques and tools used are observation, interviews, literature studies, documentation studies, observation guidelines, and questionnaires. The results showed that compensation has a positive influence on employee performance at Bukit Raya Sekawan Mining Company. Therefore, Bukit Raya Sekawan Mining Company must monitor and evaluate employee compensation and performance and make efforts to optimize the achievement of company goals and ensure employee welfare. Bukit Raya Sekawan Mining Company also needs to collect accurate information to employees about the compensation system, especially regarding health benefits to employees. That way, it is expected that Bukit Raya Sekawan Mining Company and employees jointly fulfill the objectives, rights, and obligations as a single entity in the future.